Sexualidad en la patología neoplásica ovárica - Olivares, M.ª Eugenia; Hernández, Vanesa (Psicooncología, 2003)
Ovarian oncologic disease can have direct and indirect repercussions on sexual response, that´s why this study pretends to identify those possible disorders. The sample is integrated by 25 women diagnosed for ovarian cancer and were assessed using a clinical interview and a specific questionnaire about sexual response. The results show the following information: the majority of these patients were diagnosed in initial phases of the disease, has suffered previous gynecological, vascular, endocrine, depressive and anxiety disorders, and have a partner at the moment of diagnosis. Moreover, and despite having received limited or no information along their lives, they do not agree with de main myths on sexuality. Treatments received in order of frequency were: surgery, chemotherapy, hormonal therapy and radiotherapy and the principal secondary effects were: menopause, fewer sexual frequency, vaginal dryness, lower sexual desire, vaginal stenosis and genital pain during intercourse. Nevertheless, these women consider their sexuality as satisfactory, despite they would make some modifications about it. In relation to sexual response phases, the only disturbance found was limited or null sexual desire. A tendency of relationship was found between time from diagnosis and the unwilling for changing any aspect of sexuality, and between male sexual dysfunction and the level of desire, satisfaction and frequency of sexual contacts after treatment. Regarding the relationship with their gynecologist, most of the women consider it as very satisfactory, although they would make some changes related to organisation, more than to medical assistance.